2019
DOI: 10.1111/jpc.14484
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to surgical antibiotic prophylaxis guidelines in children: A cohort study

Abstract: Aims: Surgical antimicrobial prophylaxis (SAP) is an important measure to reduce post-operative infections. Guidelines exist, but their efficacy and performance in children is poorly understood compared with adults. To review adherence to SAP guidelines, this study assesses risk factors for non-adherence and rate of early post-surgical infections. Methods: A retrospective cohort study of paediatric surgical cases (0-<18 years) at a tertiary children's hospital was performed. Patient characteristics, surgical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The antibiotic choice was not in accordance with national [ 24 ] and international guidelines [ 8 , 25 , 26 , 27 ] in almost one out of five of the procedures. This finding is in line with data presented in the literature [ 12 , 16 , 18 , 28 , 29 ]. Choosing an appropriate antibiotic is a critical issue in the correct implementation of SAP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The antibiotic choice was not in accordance with national [ 24 ] and international guidelines [ 8 , 25 , 26 , 27 ] in almost one out of five of the procedures. This finding is in line with data presented in the literature [ 12 , 16 , 18 , 28 , 29 ]. Choosing an appropriate antibiotic is a critical issue in the correct implementation of SAP.…”
Section: Discussionsupporting
confidence: 93%
“…Despite several studies focused on antibiotic prescribing habits in conjunction with surgeries in different countries having been recently published [ 16 , 17 , 18 ], little is known regarding the factors associated with SAP compliance in elective minor surgery [ 19 , 20 , 21 ]. Consequently, it is imperative to acquire such information.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to evaluate the impact of adherence to ACS recommendations for surgical antimicrobial prophylaxis (including timing, dosing, and redosing) and the development of SSI in pediatric patients. Mohamed Rizvi et al reported low adherence to guidelines for antimicrobial surgical prophylaxis in pediatric patients (39.6%) but did not evaluate the association between adherence and the development of SSI [ 16 ]. Bardia et al found poor adherence to guidelines (overall 35.9%, 19.7% for antibiotic choice, 17.1% for weight-adjusted dosing, 0.6% for timing of the first dose, and 26.8% for redosing) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,111 Despite these considerations, many studies have demonstrated that even when such protocols and guidelines exist, they are often poorly adhered to. [112][113][114][115][116][117][118][119][120] Studies investigating the implementation of AMS programs in the surgical setting have shown improved guideline adherence in several studies. [121][122][123] Segala et al found that prior to the implementation of stewardship programs, antimicrobial prophylaxis was either not required, or appropriate but not given, occured 41% of the time and that 29% of the cases were prescribed for longer than indicated.…”
Section: Antimicrobial Stewardship Programs Clinical Practice Guidelines and Protocolsmentioning
confidence: 99%